ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA DENGAN METODE HIRARC PADA PROSES PRODUKSI INDUSTRI TAHU TAHUN 2021 - Bella Rossalama Irwanda; Suprijandani; Demes Nurmayanti (Gema Lingkungan Kesehatan, 2022)
The tofu industrial production process has not implemented Occupational Health and Safety (OHS) properly and there is an OHS risk. Insufficient air circulation, noise from boiler engines, non-ergonomic posture of workers, and not using PPE while working can potentially cause work accidents. The purpose of this study was to assess the OHS risk using the HIRARC method in the tofu production process. This type of research is descriptive of occupational safety and health risks using the HIRARC method through 3 stages including identification of OHS hazards, OHS risk assessment and OHS risk control. Collecting data by observation and interviews. The sample used by all employees in the production process was 21 people. Data were analyzed descriptively by describing OHS risk using the HIRARC method through 3 stages, namely identification of OHS hazards, OHS risk assessment, and OHS risk control. The results of the physical hazard research are 50% (moderate) in the form of noise, heat/temperature, vibration. The chemical hazard is 33.33% (moderate) in the form of flammable and oxidizing chemicals. Ergonomics hazard is 83.33% (height) in the form of non-neutral sitting and standing positions, excessive workload, working hours exceeding 8 hours a day. The risk assessment obtained a moderate level of risk category (Medium). Administrative control is in the form of job rotation and job training, while PPE control is in the form of foot protectors. OHS risk analysis using the HIRARC method obtained an assessment that the most dominant OHS hazard is ergonomic hazard. OHS risk assessment obtained a moderate risk level (Medium). Administrative control and PPE control can be said to have not been implemented. Suggestions given to the company are measuring external environmental factors, monitoring and evaluating risks, making SOPs for controlling OHS risks and providing PPE for workers.